The Impact of Corruption Perception Index, Foreign Direct Investment and Economic Freedom on Economic Growth in Asean Countries 2012-2021 - Hidayati, Yuli Nurul; Bashir, Abdul (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of Corruption Perceptions Index , Foreign Direct Investment and Economic Freedom on economic growth in ASEAN countries . The data used is secondary data obtained from the world bank , transparency international and the heritage foundation for the period 2012 to 2021. The data analysis technique used is Panel Data Regression Analysis. Based on the research results , it was found that the Corruption Perception Index had a negative and insignificant impact on economic growth . Meanwhile, the Foreign Direct I nvestment variable has a significant positive relationship and the Economic Freedom variable produces a significant negative relationship with economic growth in ASEAN member countries.